Визначення впливу рівня енергонасиченості колісного трактора на силу опору його коченню - Надикто, Володимир Трохимович; Кюрчев, Володимир Миколайович; Погорілий, Сергій Петрович; Nadykto, Volodymyr; Kyurchev, Volodymyr; Pohorilyi, Sergiy (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Метою роботи є з’ясування впливу енергонасиченості колісного трактора на величину сили опору його коченню. Для її досягнення проведено теоретичні й експериментальні дослідження з використанням основ теорії трактора щодо закономірностей перебігу його тягового балансу. У підсумку здійснено аналіз функціонального ланцюжка у вигляді «збільшення рівня енергонасиченості трактора (параметр Ен) – зростання швидкості руху енергетичного засобу (параметр V ) – зростання тягового опору агрегата (параметр Ркр)». Установлено, що зростання значення сили Ркр від параметра V за законом параболи за певних умов може викликати як зменшення, так і збільшення значення сили опору коченню трактора. Зростання рівня параметра Ен залежно від зумовленого цим процесом збільшення швидкості руху енергетичного засобу може спричиняти як зростання, так і зменшення сили опору його кочення (Pf ). За умови паритетного впливу зміни значень параметрів Ен і V на величину сили Pf її значення може бути інваріантним відносно зміни рівня енергонасиченості трактора. Установлення однозначності впливу рівня енергонасиченості трактора на величину його опору коченню потребує проведення фундаментальних наукових досліджень. /// EN: The goal of this article is to investigate the impact of energy saturation on the magnitude of rolling resistance in a wheeled tractor. Theoretical studies were conducted using the basics of tractor theory in terms of the regularities of its traction balance. Experimental studies were performed using strain gauge equipment and the Arduino Uno microcontroller. Experimental data were processed in Microsoft Excel and Grapher 17 software and graphics environments. The functional chain was analyzed in the form of “increase in the level of tractor energy saturation (parameter En) – increase in the speed of the energy vehicle movement (parameter V) – increase in the traction resistance of the unit (parameter Pkp)”. It was established that an increase in the value of the force Pkr from the parameter V, according to the law of the parabola, under certain conditions can cause both a decrease and an increase in the value of the tractor’s rolling resistance force. An increase in the level of the parameter En, resulting from the speed of movement of the energy vehicle, can cause both an increase and a decrease in the force of its rolling resistance (Pf). Under the condition of parity, the influence of changes in the values of the parameters En and V on the value of the force Pf can be invariant with respect to changes in the level of tractor energy saturation. Establishing the uniqueness of the influence of the level of tractor energy saturation on the value of its rolling resistance requires conducting fundamental scientific research.
Determining the influence of the wheeled tractor energy saturation level on its rolling resistance
Keywords: тяговий баланс; тягове зусилля; тяговий опір; рушій; швидкість руху; вертикальне навантаження; traction balance; traction force; traction resistance; engine; speed; vertical load